1994
DOI: 10.1016/0266-7681(94)90221-6
|View full text |Cite
|
Sign up to set email alerts
|

The Palmar Fascia after Treatment by the Continuous Extension Technique for Dupuytren’s Contracture

Abstract: After complete elongation using the continuous extension technique the palmar fascia of four patients with Dupuytren's contracture was examined by light and electron microscopy and compared with non-elongated samples from 20 patients at the same clinical stage of the disease. Nodules and cords were no longer clinically recognizable after extension. The tissue contained collagen fibrils of uniform diameter (about 50 nm), densely packed in fibres parallel to the stretching force. Fine filaments (presumably prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…An extension torque about the joint transmits tension forces to both the diseased Dupuytren tissues as well as all other contracted palmar tissues, causing these tissues to increase in length over time. 1,2 It is difficult to determine the etiology of every PIP joint contracture and assess whether the Digit Widget is appropriate; nevertheless, it has been used successfully in reversing PIP joint contractures associated with Dupuytren disease. 3…”
mentioning
confidence: 99%
“…An extension torque about the joint transmits tension forces to both the diseased Dupuytren tissues as well as all other contracted palmar tissues, causing these tissues to increase in length over time. 1,2 It is difficult to determine the etiology of every PIP joint contracture and assess whether the Digit Widget is appropriate; nevertheless, it has been used successfully in reversing PIP joint contractures associated with Dupuytren disease. 3…”
mentioning
confidence: 99%
“…However, we do not know what would have happened if they had not used the splint as they did. Another explanation could be that the external extension force generated by the splint actually stimulated neoformation and reorientation of the tissue components by myofibroblasts as mentioned previously (4). We also have to consider whether the splint was applied too late at two to three weeks after operation.…”
Section: Discussionmentioning
confidence: 95%
“…A number of traction or extension techniques and splinting programmes has been developed to try and improve this, including dynamic splinting (1,2,4,9,13,14). These techniques can be used as an adjunct to operation when the contraction deformity is stretched before operation to facilitate the dissection (1,4,13). Others use postoperative dynamic extension splinting (2,14).…”
mentioning
confidence: 99%
“…Bailey et al (1994) reported on the biochemical changes in the tissues during distraction, and found increased levels of degradative enzymes such as neutral metalloproteinases (collagenase and gelatinase) and the acidic cathepsins B and L. Both these groups of enzymes depolymerize collagen fibers causing a loss of tensile strength and its resorption. Brandes et al (1994) performed electron microscopy studies of Dupuytren's tissue after distraction and compared this tissue with standard Dupuytren's tissue from patients with the same clinical stage of the disease. Brandes et al (1994) performed electron microscopy studies of Dupuytren's tissue after distraction and compared this tissue with standard Dupuytren's tissue from patients with the same clinical stage of the disease.…”
Section: Discussionmentioning
confidence: 99%